Tag retention in and effects of passive integrated transponder tagging on survival and swimming performance of a small‐bodied darter. Issue 3 (6th January 2022) - Swarr, Tyler R.; Myrick, Christopher A.; Fitzpatrick, Ryan M.
Abstract: Fisheries biologists have been hesitant to use passive integrated transponder (PIT) tags in small‐bodied fishes (40–200 mm TL) such as darters (Percidae: Etheostomatinae) because of the fishes' size and potential effect on swimming performance. The authors used constant acceleration trials to evaluate the swimming performance of Arkansas darters Etheostoma cragini in control (no incision or tag), sham (incision and suture) or PIT tagged (surgically implanted 8 × 1.4 mm intra‐peritoneal PIT tag) treatments. Tag retention and fish survival were monitored for up to 199 days post‐tagging. Maximum swimming velocity did not differ between control, sham and PIT tag treatments, nor was maximum swimming velocity affected by the tagging procedure. Tag retention was 100%, and the overall survival of tagged fish was 88% in the swimming study, and 100% in the long‐term study, suggesting that small PIT tags are suitable for use in darters. The authors include a brief meta‐analysis on the results reported by 20 studies that PIT tagged small‐bodied fishes, representing 38 species and nine families of freshwater fish.